2022
DOI: 10.3389/fmars.2022.975716
|View full text |Cite
|
Sign up to set email alerts
|

Phenological divergence, population connectivity and ecological differentiation in two allochronic seabird populations

Abstract: Phenological divergence between conspecific populations breeding sympatrically is increasingly recognized as an important evolutionary process that may lead to allochronic speciation. However, the extent to which adaptation to differences in the timing of breeding may contribute to this process remains unclear. In this study, we assessed breeding phenology, population connectivity, and niche differentiation of two allochronic populations we of the Cape Verde Storm-petrel (Hydrobates jabejabe). We monitored nes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…This pattern is well-documented for seabirds, such as gadfly petrels (Pastor-Prieto et al ., 2019) and little shearwaters (Ramos et al ., 2020). However, previous studies on Storm-petrels of the family Hydrobatidae have shown a weak relationship between activity and moon brightness (e.g., Militão et al ., 2022; Medrano et al ., 2022). Further research is needed to understand if the foraging behaviour of the Hydrobatidae and Oceanitidae storm-petrels families usually differ, which may reflect trophic differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern is well-documented for seabirds, such as gadfly petrels (Pastor-Prieto et al ., 2019) and little shearwaters (Ramos et al ., 2020). However, previous studies on Storm-petrels of the family Hydrobatidae have shown a weak relationship between activity and moon brightness (e.g., Militão et al ., 2022; Medrano et al ., 2022). Further research is needed to understand if the foraging behaviour of the Hydrobatidae and Oceanitidae storm-petrels families usually differ, which may reflect trophic differences.…”
Section: Discussionmentioning
confidence: 99%
“…We analysed changes in the daily proportion of time spent on the water, based on wet-dry data collected in the geolocators, under the assumption that it is an indicator of resting sessions (e.g., Militão et al ., 2022; Medrano et al ., 2022) during the non-breeding period. Two of the six tracks from the geolocators had incomplete wet-dry data (due to memory issues) and were excluded from the activity patterns analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cabo Verde, consists of 10 volcanic islands that lie between 600 and 850 km west of Senegal, Africa (Figure 1a,c), located at the eastern boundary of the North Atlantic subtropical gyre at the southern limit of the Canary Current (Fernandes et al., 2005). The waters around St Helena are characterised by a generally low chlorophyll a concentration with substantial variation in spatial distribution between years (maximum range 0.3–0.5 mg/m 3 ) (Thorpe et al., 2020), whereas Cabo Verde is considered a more productive oceanic region with more enriched waters (chlorophyll a concentration range 0.06–4.1 mg/m 3 (Medrano et al., 2022; Silva, 2022; Vieira, 2019)).…”
Section: Methodsmentioning
confidence: 99%